Atomistic insights into the effects of Cr content on CoCrxFeNiTi tribological behavior: a molecular dynamics study - Maoli Yang; Fenghua Liu; Yubo Hua; Zongbi Huang; Zhongwei Liang; Fuchuan Huang; Gongbin Tang (Materials & Design)
CoCrFeNiTi high-entropy alloys (HEAs) have attracted considerable attention, yet the atomic-scale tribological behavior remains poorly understood. Here, molecular dynamics simulations were employed to investigate the effect of Cr content on the tribological performance of CoCrFeNiTi HEAs. Compared to CoFeNiTi, adding 35 at% Cr reduces worn atoms by 65.8 %, frictional force by 22.5 %, and the friction coefficient by 23.0 %. Detailed analysis reveals that higher Cr content enhances strength and ductility, while friction-induced surface dislocations promote the formation of additional Cr-M (M = Co, Fe, Ni) bonds in the wear track, improving strength, hardness, and wear resistance. This study offers atomic-scale insights into the role of Cr in the tribological performance of CoCrFeNiTi HEAs, providing theoretical guidance for alloy design and optimization.